Synthesis and characterization of tumor-targeted copolymer nanocarrier modified by transferrin - Liu R; Wang Y; Li X; Bao W; Xia G; Chen W; Cheng J; Xu Y; Guo L; Chen B (Dove Medical Press, 2015)
Ran Liu,1,2 Yonglu Wang,1,3 Xueming Li,3 Wen Bao,1,2 Guohua Xia,1,2 Wei Chen,3 Jian Cheng,1,2 Yuanlong Xu,3 Liting Guo,1,2 Baoan Chen1,21Department of Hematology (Key Department of Jiangsu Medicine), Zhongda Hospital, Medical School, 2Faculty of Oncology, Medical School, Southeast University, 3College of Pharmacy, Nanjing University of Technology, Nanjing, People’s Republic of China Abstract: To increase the encapsulation of hydrophilic antitumor agent daunorubicin (DNR) and multidrug resistance reversal agent tetrandrine (Tet) in the drug delivery system of nanoparticles (NPs), a functional copolymer NP composed of poly(lactic-co-glycolic acid) (PLGA), poly-l-lysine (PLL), and polyethylene glycol (PEG) was synthesized and then loaded with DNR and Tet simultaneously to construct DNR/Tet–PLGA–PLL–PEG-NPs using a modified double-emulsion solvent evaporation/diffusion method. And to increase the targeted antitumor effect, DNR/Tet–PLGA–PLL–PEG-NPs were further modified with transferrin (Tf) due to its specific binding to Tf receptors (TfR), which is highly expressed on the surface of tumor cells. In this study, the influence of the diversity of formulation parameters was investigated systematically, such as drug loading, mean particle size, molecular weight, the concentration of PLGA–PLL–PEG–Tf, volume ratio of acetone to dichloromethane, the concentration of polyvinyl alcohol (PVA) in the external aqueous phase, the volume ratio of the internal aqueous phase to the external aqueous phase, and the type of surfactants in the internal aqueous phase. Meanwhile, its possible effect on cell viability was evaluated. Our results showed that the regular spherical DNR/Tet–PLGA–PLL–PEG–Tf-NPs with a smooth surface, a relatively low polydispersity index, and a diameter of 213.0±12.0 nm could be produced. The encapsulation efficiency was 70.23%±1.91% for DNR and 86.5%±0.70% for Tet, the moderate drug loading was 3.63%±0.15% for DNR and 4.27%±0.13% for Tet. Notably, the accumulated release of DNR and Tet could be sustained over 1 week, and the Tf content was 2.18%±0.04%. In cell viability tests, DNR/Tet–PLGA–PLL–PEG–Tf-NPs could inhibit the proliferation of K562/ADR cells in a dose-dependent manner, and the half maximal inhibitory concentration value (total drug) of DNR/Tet–PLGA–PLL–PEG–Tf-NPs was lower than that of DNR, a mixture of DNR and Tet, and DNR/Tet–PLGA–PLL–PEG-NPs. These results clearly indicate that the PLGA–PLL–PEG formulation is a potential drug delivery system for hydrophilic and hydrophobic drugs, and that Tf modification may increase its targeting properties. Keywords: PLGA, PLL, PEG, daunorubicin, tetrandrine